Medicine and narration in the eighteenth century - Vasset, S (Voltaire Foundation, 2017)
How did doctors argue in eighteenth-century medical pamphlet wars? How literary, or clinical, is Diderot’s depiction of mad nuns? What is at stake in the account of a cataract operation at the beginning of Jean-Paul’s novel Hesperus? In this pioneering volume, contributors extend current research at the intersection of medicine and literature by examining the overlapping narrative strategies in the writings of both novelists and doctors. Focusing on a wide variety of sources, an interdisciplinary team of researchers explores the nature and function of narration as an underlying principle of such writing. From a reading of correspondence between doctors as a means of continuing professional education, to the use of inoculation as a plotting device, or an examination of Diderot’s physiological approach to mental illness in La Religieuse, contributors highlight: • how doctors exploited rhetorical techniques in both clinical writing and correspondence with patients. • how novelists incorporated medical knowledge into their narratives. • how models such as case-histories or narrative poetry were adopted and transformed in both fictional and actual medical writing. • how these narrative strategies shaped the way in which doctors, patients and illnesses were represented and perceived in the eighteenth century. Sophie Vasset, Introduction: questions of narration in eighteenth-century medicine and literature I. Medical storytelling: case studies and anecdotes Alexandre Wenger, From medical case to narrative fiction: Diderot’s La Religieuse Sophie Vasset, How to relate a medical case: the controversy about John Ranby’s Narrative of the last illness of the earl of Orford (1745) II. The doctor’s letters: epistolary narration Philip Rieder, Writing to fellow physicians: literary genres and medical questions in Louis Odier’s (1748-1817) correspondence David Shuttleton, ‘Not the meanest part of my works and experience’: Dr George Cheyne’s correspondence with Samuel Richardson Hélène Dachez and Sophie Vasset, Clementina’s disease and polyphonic narration in Samuel Richardson’s Sir Charles Grandison (1754) III. Illness as narrative Rudy Le Menthéour, Melancholy vaporised: self-narration and counter-diagnosis in Rousseau’s work Catriona Seth, Textually transmitted diseases: smallpox inoculation in French literary and medical works Gavin Budge, Smollett and the novel of irritability IV. Medical strategies and narrative devices Sylvie Kleiman-Lafon, The healing power of words: medicine and literature in Bernard Mandeville’s Treatise of the hypochondriack and hysterick diseases Helge Jordheim, Oculist narratives in late-eighteenth-century Germany: from cataract surgery to political conspiracy in Jean Paul’s Hesperus Hugues Marchal, ‘Le poète raconte et ne discute pas’: poetic and medical codes in Jean-François Sacombe’s obstetric epic, La Luciniade (1792-1815) Summaries Bibliography Index